2016
DOI: 10.1590/0103-6440201600715
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of Cultivable Bacteria From Infected Root Canals Associated With Acute Apical Abscess

Abstract: The objective of this study was to investigate the bacterial composition present in root canals of teeth associated with acute apical abscess by molecular identification (16S rRNA) of cultivable bacteria. Two hundred and twenty strains isolated by culture from 20 root canals were subjected to DNA extraction and amplification of the 16S rRNA gene (PCR), followed by sequencing. The resulting nucleotide sequences were compared to the GenBank database from the National Center of Biotechnology Information through B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 29 publications
2
34
0
Order By: Relevance
“…Even considering the limitations of sampling biofilms by using endodontic files/paper points, this approach is a well‐established protocol because all floating species present in the main RC/PP are or were members of the endodontic/periodontal biofilm . For assessment of microbiota in PP and/or RC, the literature has reported several studies using sterile paper points for sample collection . In addition, VMGA III is frequently used as transport medium, which avoids bacterial loss from PP and RC samples until laboratorial procedures …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even considering the limitations of sampling biofilms by using endodontic files/paper points, this approach is a well‐established protocol because all floating species present in the main RC/PP are or were members of the endodontic/periodontal biofilm . For assessment of microbiota in PP and/or RC, the literature has reported several studies using sterile paper points for sample collection . In addition, VMGA III is frequently used as transport medium, which avoids bacterial loss from PP and RC samples until laboratorial procedures …”
Section: Discussionmentioning
confidence: 99%
“…For assessment of microbiota in PP and/or RC, the literature has reported several studies using sterile paper points for sample collection . In addition, VMGA III is frequently used as transport medium, which avoids bacterial loss from PP and RC samples until laboratorial procedures …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite, the rapid evolution in irrigating materials, devices, and tools, the persistence of bacteria remains questionable. The diversity of root canal anatomy and the organisation of microorganisms hindered in the dentinal tubules, isthmuses and ramifications complicate the complete bacterial eradication from root canal which usually ends with apical periodontitis [2, 14]. It was confirmed that there is an actual relationship between the presence of specific bacterial taxa in filled root canal and treatment failure, which suggested that some taxa, such as streptococci, Olsenella uli, Propionibacterium acnes , and Fusobacterium nucleatum , might have the potentiality to be the initiator of risk factors and cause periapical diseases [15].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus may act as a precursor for inducing pulp necrosis and successive periapical lesions and failed endodontic treatment cases due to altered wound repair, immune and vascular functions [1, 2]. …”
Section: Introductionmentioning
confidence: 99%